Abundance, activity patterns and microhabitat of Rhinella macrorhina, an endemic toad from the cloud forests of the Colombian Central Andes (2009)
ABSTRACT: The high proportion of declining amphibian populations and species without ecological information makes it imperative to conduct research on their population biology, natural history and habitat requirements. We describe the abundance, age structure, activity patterns and microhabitat of four populations of Rhinella macrorhina, a threatened toad from the cloud forests of the Andes of Colombia. We found similar abundances in all populations, despite differences in the level of alteration of the forest patches studied. Abundance of the species was higher during the rainy season and was related to leaf litter depth and leaf litter humidity. We found similar proportions of adults and juveniles among seasons in all populations, and we suggest that daily activity of R. macrorhina varies by age class, exhibiting a temporal and spatial segregation. We present insight into habitat alteration which may threaten the species, principally in the Amalfi locality where we report the largest documented population of the species.